Consumption of Coffee and Risk of Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis of Observational Studies - Ni, Jiaying; Wang, Ping; Zheng, Tao; Lv, Long; Peng, Hao (Frontiers in Nutrition, 2021)
Objective: The results from epidemiologic studies on the relationship between coffee intake and the risk of gestational diabetes mellitus (GDM) remain inconclusive. We performed a meta-analysis to achieve a comprehensive finding regarding the association between coffee intake and the risk of GDM. Methods: PubMed, Scopus, ISI Web of Science, and Google Scholar were searched to find articles published up to August 2021. Observational studies which reported risk estimates (Risk Ratios (RRs), Hazard Ratios (HRs) and Odds Ratios (ORs)) for the association of coffee consumption with risk of GDM in pregnant women were included. Random effects model was applied to calculate summarized risk estimate and 95% confidence intervals (CIs) for the highest versus lowest categories of coffee intake. Results: Seven observational studies (three cohort, two case-control, and two cross-sectional studies) with 75607 participants and 1625 women with GDM met the inclusion criteria. The meta-analysis of comparing highest versus lowest coffee intake categories showed no significant association between coffee intake and risk of GDM (Summarized Risk Estimate: 0.89; 95% CI: 0.76, 1.05; I2 = 63.4 %). Subgroup analysis showed that coffee consumption had an inverse relationship with GDM in studies conducted in non-Asia countries(Summarized Risk Estimate: 0.75; 95% CI: 0.58, 0.97; I2 = 6 %). Conclusion: This study has shown that high coffee consumption did not decrease the risk of GDM. Further large-scale cohort studies are required to confirm our findings.